SMOKING AS AN UNFAVORABLE LIFESTYLE FACTOR FOR THE PROGRESSION OF PRIMARY OPEN-ANGLE GLAUCOMA - Clivia Erb; Alibek Amandykov; Carl Erb (Interdisciplinary Approaches to Medicine, 2025)
Introduction: Smoking remains a widely used and socially accepted psychoactive substance. According to a July 2024 national survey by the Bureau of National Statistics of Kazakhstan, 20.7% of the adult population are smokers—39.8% of men and 7.6% of women.Smoking is the leading preventable health risk and a major cause of premature death, associated with increased rates of cardiovascular, respiratory, gastrointestinal, endocrine diseases, and cancer.